LncRNA SNHG6 sponges miR-101 and induces tamoxifen resistance in breast cancer cells through induction of EMT - Khan, Mohammad Imran; Ahmad, Aamir (Frontiers in Oncology, 2022)
Acquired resistance is a major clinical challenge for tamoxifen-based therapy. In this study, we focused on lncRNA SNHG6 which plays a role in chemoresistance of cancer cells, but has never been investigated in the context of tamoxifen resistance. We found elevated levels of SNHG6 in tamoxifen-resistant estrogen receptor (ER)-positive MCF-7 cells (MCF7TR), relative to naïve MCF-7 cells, as well as in tamoxifen-resistant T47D cells (T47DTR), relative to naïve T47D cells, which correlated with induced vimentin, ZEB1/2 and decreased e-cadherin, thus implicating a role of EMT in SNHG6-mediated tamoxifen resistance. Downregulation of SNHG6, using specific siRNA, sensitized MCF7TR as well as T47DTR cells to tamoxifen along with markedly reduced proliferation, invasion and anchorage-independent clonogenicity. Further, SNHG6 was found to sponge and inhibit miR-101 as the endogenous expression levels of SNHG6 and miR-101 inversely correlated in paired parental and tamoxifen-resistant cells and, moreover, silencing of SNHG6 in tamoxifen-resistant cells resulted in de-repression of miR-101, along with reversal of EMT. SNHG6 expression also directly correlated with increased stem cells markers Sox2, Oct4 and EZH2. miR-101 levels, manipulated by transfections with pre/anti-miR-101 oligos, directly affected tamoxifen sensitivity of ER-positive cells with pre-miR-101 sensitizing MCF7TR and T47DTR cells to tamoxifen whereas anti-miR-101 inducing resistance of parental MCF-7 and T47D cells to tamoxifen. Further, miR-101 was found to attenuate SNHG6-mediated effects on tamoxifen resistance, EMT as well as stem cell markers, thereby making a case for SNHG6-miR-101 axis in tamoxifen resistance of ER-positive breast cancer cells. Thus, lncRNA SNHG6 is a novel modulator of tamoxifen resistance through its sponging of miR-101 and the resulting effects on EMT.